2022
DOI: 10.3390/math10050720
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Asymmetric Relationship between Economic Policy Uncertainty, Cryptocurrencies, and Global Green Bonds? Evidence from the United States of America

Abstract: The environmental degradation and the concern for sustainable development have garnered extensive attention from researchers to evaluate the prospects of green bonds over other traditional assets. Against this backdrop, the current study measures the asymmetric relationship between green bonds, U.S. economic policy uncertainty (EPU), and bitcoins by employing the Nonlinear Autoregressive Distribution Lag (NARDL) estimation technique recently developed by Shin et al., (2014). The outcome of the empirical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Stationarity checks are not mandatory for applying NARDL models, as suggested by previous studies ( Abbasi et al, 2022 ; Amin et al, 2022 ). However, as highlighted by some studies, this model is not suitable for second-order integrals because the results of the bound F statistic become invalid in the case of I (2; Alqahtani et al, 2020 ; Syed, 2021a , b ; Syed et al, 2021b , 2022 ; Bertsatos et al, 2022 ; Xia et al, 2022 ). Hence, this study used three different unit root tests, the DF-GLS test proposed by Elliot et al (1996) , Augmented Dickey Fuller (ADF) Dickey and Fuller (1981) , and Phillips and Perron (PP) Phillips and Perron (1988) to test variable integrals.…”
Section: Analysis Results and Interpretationmentioning
confidence: 99%
“…Stationarity checks are not mandatory for applying NARDL models, as suggested by previous studies ( Abbasi et al, 2022 ; Amin et al, 2022 ). However, as highlighted by some studies, this model is not suitable for second-order integrals because the results of the bound F statistic become invalid in the case of I (2; Alqahtani et al, 2020 ; Syed, 2021a , b ; Syed et al, 2021b , 2022 ; Bertsatos et al, 2022 ; Xia et al, 2022 ). Hence, this study used three different unit root tests, the DF-GLS test proposed by Elliot et al (1996) , Augmented Dickey Fuller (ADF) Dickey and Fuller (1981) , and Phillips and Perron (PP) Phillips and Perron (1988) to test variable integrals.…”
Section: Analysis Results and Interpretationmentioning
confidence: 99%
“…This variable can be used as a proxy for green markets. In contrast, Syed et al (2022) employing the Nonlinear Autoregressive Distribution Lag (NARDL) for studying the dynamic linkage between the oil price and green bonds, concluded that oil prices positively influence the green bonds performance. The study found that a 1 percent increase (decrease) in oil prices increases (decreases) the performance of green bonds by 0.05 percent.…”
Section: Dynamic Conditional Correlations Among the Variablesmentioning
confidence: 99%
“…The United States is the source of the majority of the economic policy uncertainty. United States economic policies will undoubtedly have a ripple impact on the world economy (Syed, Ahmed, Kamal, Ullah, & Ramos-Requena, 2022). The shock that was generated was similar to American policies which had a significant impact on the ASEAN economy (Murshed & Tanha, 2021).…”
Section: Introductionmentioning
confidence: 99%